PROSES PEMBELAJARAN OPERASI PENGURANGAN BERBANTUAN MEDIA TABUNG PENGURANGAN PADA KELAS I SDN MOJOLANGU 3 - Ahmad Yulianto (STKIP Andi Matappa Pangkep, 2018)
This research is aimed to describe the use of subtraction tube media in teaching subtraction at the first grade students of Elementary School 3 Malang City. The design of this research used qualitative design within descriptive method to describe the teacher and students’ activities in learning process based on lesson study with some steps, they are (1)planning, implementation, and reflexive. The use of subtractive tube media in teaching subtraction could make the students active in learning process. Besides, the subtraction tube could improve the students score and lead them to find the answer of the question by themselves in order to make the lesson become more interactive and meaningful.